Unveiling the Role of CNTs in the Phase Formation of One-Dimensional Ferroelectrics - Mahajan, Amit (Langmuir : the ACS journal of surfaces and colloids, 2015)
Carbon nanotubes (CNTs) have the potential to act as templates or bottom electrodes for three-dimensional (3D) capacitor arrays, which utilize one-dimensional (1D) ferroelectric nanostructures to increase the memory size and density. However, growing a ferroelectric on the surface of CNTs is nontrivial. Here, we demonstrate that multiwalled (MW) CNTs decrease the time and temperature for the formation of lead zirconium titanate Pb(Zr1-xTix)O3 (PZT) by ∼100 °C commensurate with a decrease in activation energy from 68 ± 15 to 27 ± 2 kJ/mol. As a consequence, monophasic PZT was obtained at 575 °C for MWCNTs/PZT, but for pure PZT, traces of pyrochlore were still present at 650 °C, where the PZT phase formed due to homogeneous nucleation. The piezoelectric nature of MWCNTs/PZT synthesized at 500 °C for 1 h was proven. Although further work is required to prove the concept of 3D capacitor arrays, our result suggests that it is feasible to utilize MWCNTs as templates/electrodes for the formation of 1D PZT nanoferroelectrics